A modified Larson's method of posterolateral corner reconstruction of the knee reproducing the physiological tensioning pattern of the lateral collateral and popliteofibular ligaments - Niki Yasuo; Matsumoto Hideo; Otani Toshiro; Enomoto Hiroyuki; Toyama Yoshiaki; Suda Yasunori (BMC, 2012)
Abstract Background Consensus has been lacking as to how to reconstruct the posterolateral corner (PLC) of the knee in patients with posterolateral instability. We describe a new reconstructive technique for PLC based on Larson's method, which reflects the physiological load-sharing pattern of the lateral collateral ligament (LCL) and popliteofibular ligament (PFL). Findings Semitendinosus graft is harvested, and one limb of the graft comprises PFL and the other comprises LCL. Femoral bone tunnels for the LCL and popliteus tendon are made at their anatomical insertions. Fibular bone tunnel is prepared from the anatomical insertion of the LCL to the proximal posteromedial portion of the fibular head, which corresponds to the insertion of the PFL. The graft end for popliteus tendon is delivered into the femoral bone tunnel and secured on the medial femoral condyle. The other end for LCL is passed through the fibular tunnel from posterior to anterior. While the knee is held in 90 of flexion, the graft is secured in the fibular tunnel using a 5 mm interference screw. Then, the LCL end is passed into the femoral bone tunnel and secured at the knee in extension. Conclusions Differential tension patterns between LCL and PFL is critical when securing these graft limbs. Intrafibular fixation of the graft using a small interference screw allows us to secure these two graft limbs independently with intended tension at the intended flexion angle of the knee.